Vitamin A and the epigenome. Issue 11 (24th July 2017) - Bar-El Dadon, Shimrit; Reifen, Ram
ABSTRACT: The epigenetic phenomena refer to heritable changes in gene expression other than those in the DNA sequence, such as DNA methylation and histone modifications. Major research progress in the last few years has provided further proof that environmental factors, including diet and nutrition, can influence physiologic and pathologic processes through epigenetic alterations, which in turn influence gene expression. This influence is termed nutritional epigenetics, and one prominent example is the regulation of gene transcription by vitamin A through interaction to its nuclear receptor. Vitamin A is critical throughout life. Together with its derivatives, it regulates diverse processes including reproduction, embryogenesis, vision, growth, cellular differentiation and proliferation, maintenance of epithelial cellular integrity and immune function. Here we review the epigenetic role of vitamin A in cancer, stem cells differentiation, proliferation, and immunity. The data presented here show that retinoic acid is a potent agent capable of inducing alterations in epigenetic modifications that produce various effects on the phenotype. Medical benefits of vitamin A as an epigenetic modulator, especially with respect to its chronic use as nutritional supplement, should rely on our further understanding of its epigenetic effects during health and disease, as well as through different generations.